PENGUKURAN KINERJA BANK DENGAN PENDEKATAN EFISIENSI : STUDI TERHADAP PERBANKAN GO-PUBLIC DI INDONESIA - Nur Febri Ainun D; Noor Shodiq Askandar; Anik Malikah (Universitas Islam Malang, 2019)
ABSTRACT Performance is one indicator of the efficiency of a company. The measurement of banking performance commonly carried out by banks is by using financial ratios. However, measuring the performance of banks using financial ratios has not been able to show the actual operating conditions of a bank. To overcome these limitations, there are methods that can measure the performance of branch offices that are capable of handling many inputs and outputs, namely the Data Envelopment Analysis (DEA) method. DEA method is a linear program that aims to maximize input and output. This study aims to analyze the health efficiency of banks listed on the IDX. Object research in this study uses 42 banks on the IDX. This study uses the Data Envelopment Analysis (DEA) method using an intermediation approach and uses output maximization. This study uses input variables consisting of savings, assets, and labor costs and uses output variables consisting of credit or financing, and income. The results showed that relatively efficient banks for 2 consecutive years were 5 banking companies that were able to properly maintain their financial stability, among others: Bank Artos Indonesia Tbk, Bank Ina Perdana, Bank Mandiri, Bank Victoria International and Bank Mayapada. Keywords: DEA (Data Envelopment Analysis), Performance Efficiency. Bank.